2016
DOI: 10.3748/wjg.v22.i34.7797
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative pancreatic fistula: Analysis of 539 successive cases of pancreaticoduodenectomy

Abstract: AIMTo analyze the risk factors for pancreatic fistula after pancreaticoduodenectomy.METHODSWe conducted a retrospective analysis of 539 successive cases of pancreaticoduodenectomy performed at our hospital from March 2012 to October 2015. Pancreatic fistula was diagnosed in strict accordance with the definition of pancreatic fistula from the International Study Group on Pancreatic Fistula. The risk factors for pancreatic fistula were analyzed by univariate analysis and multivariate logistic regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 46 publications
(36 reference statements)
4
105
2
Order By: Relevance
“…RPV is associated with pancreatic fluid volume and drainage fluid amylase activity, consistent with the hypothesis that patients with a greater pancreatic parenchymal remnant volume have a greater volume of pancreatic fluid secretion, resulting in a greater rate of clinically relevant POPF [12]. In addition, increased RPV values showed a positive correlation with a soft pancreatic texture and a small main pancreatic duct size (≤3.0 mm) [7, 8, 29]. Indeed, in the present study, we also found significant differences in pancreas texture ( p < 0.01) and main pancreatic duct diameter ( p < 0.01) between the low- and high-RPV groups.…”
Section: Discussionsupporting
confidence: 57%
“…RPV is associated with pancreatic fluid volume and drainage fluid amylase activity, consistent with the hypothesis that patients with a greater pancreatic parenchymal remnant volume have a greater volume of pancreatic fluid secretion, resulting in a greater rate of clinically relevant POPF [12]. In addition, increased RPV values showed a positive correlation with a soft pancreatic texture and a small main pancreatic duct size (≤3.0 mm) [7, 8, 29]. Indeed, in the present study, we also found significant differences in pancreas texture ( p < 0.01) and main pancreatic duct diameter ( p < 0.01) between the low- and high-RPV groups.…”
Section: Discussionsupporting
confidence: 57%
“…Based on the fact that CR-POPF potentially causes subsequent critical postoperative complications such as intraabdominal abscess and pseudoaneurysm associated with postpancreatectomy hemorrhage, both predicting and treating CR-POPF are clinically significant issues. With regard to its prediction, owing to previous studies some factors have been identified as being predictive for CR-POPF development such as body mass index, indication disease for the surgical treatment, diameter of the main pancreatic duct, texture of the pancreatic parenchyma, and amount of intraoperative bleeding (7)(8)(9)(10)(11)16,17). On the other hand, few studies have focused on treatment of CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying patients at high risk for developing CR-POPF is considered important for improving the clinical outcome in patients undergoing PD. In this regard, many studies have identified predictive factors for developing CR-POPF such as body mass index, diameter of the main pancreatic duct (MPD), and pancreatic consistency (7)(8)(9)(10)(11). In addition to such predictors of CR-POPF development, treatment of POPF after it develops is also important for improving clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter has been purposed as predictive factor for risk of fistula in previous series, but no accordance has been reached for the best cut-off value. [21][22][23][24] Metabolic status assessment have been demonstrated as a predictive factor for outcome in patients with pancreatic cancer and other neoplasms, affecting overall survival and disease free survival; the most common parameter analysed as expression of metabolic status is serum albumin. 20 POD3 amylase level in drainage fluid appears to be more predictive in our study than POD1 level probably because amylase levels in the drain effluent on POD1 may reflect alleged transient pancreatic leakage from the right-angle branches.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nutritional and metabolic status is still controversial in large series analysing risk factors for POPF. [21][22][23][24] Metabolic status assessment have been demonstrated as a predictive factor for outcome in patients with pancreatic cancer and other neoplasms, affecting overall survival and disease free survival; the most common parameter analysed as expression of metabolic status is serum albumin. [7][8][9] The present study showed a significant correlation between POD1 serum albumin and POPF at univariate analysis, while preoperative values didn't show significant differences between patients with and without POPF ( Table 2); these data have been previously reported in large series but not confirmed in randomized trials.…”
Section: Discussionmentioning
confidence: 99%